HUBUNGAN BEBERAPA FAKTOR IBU DENGAN KEJADIAN KELAHIRAN MATI (STILLBIRTHS) DI KECAMATAN CILONGOK KABUPATEN BANYUMAS TAHUN 2016 - Nisriina Rahayuni Utami; Djoko Nugroho; Yudhy Dharmawan; Sri Winarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Stillbirth and maternal mortality rates were strongly correlated, with about 5 stillbirths for each maternal death. In 2015, Banyumas has the highest births death rate at central java. Cilongok is the region in Banyumas who has highest stillbirth rate with 10,3 per 1000 births in 2016. The purpose of this study is to analyze the relationship of maternal factors with stillbirths in sub district Cilongok Banyumas in 2016. The type of this research is explanatory research using case control study with retrospective approachment. The population is 1942 maternal who gave birth at 2016 with 15 case samples and 30 control samples. Selection of control samples using simple random sampling. The results showed that the highest percentage of mothers were age at no risk (66.7%), have further education (57.8%), unemployment (64.4%), have disease history (53.3%), parity at 1 and 2 (73.3%), visited ANC (100%) and the first ANC visit was not late (88.9%). Chi Square analysis with yates correction showed that there is no relationship between maternal age (pvalue 1,000), maternal education level (pvalue 0,455), maternal occupational status (pvalue 1,000), maternal disease history (pvalue 0,751), parity (pvalue 0,721), visit of ANC (Pvalue -), the first ANC visit (pvalue 1,000) with stillbirths in sub-district Cilongok, Banyumas in 2016. Screening and direct visit from the village midwife to maternal needs to be done to increase the number of ANC visits during the first 3 months of pregnancy.